Preparation method of high-purity aluminum target material
By using three annealing combined with hot rolling and cold rolling during the preparation process of high-purity aluminum targets, the problem of uneven grains of high-purity aluminum targets is solved, and large size and high mechanical properties are achieved and high-purity aluminum targets with good sputtering performance.
Patent Information
- Application Number
- CN202411567544.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The structure formed by high-purity aluminum targets during solidification is relatively coarse, making it difficult to obtain large-size high-purity aluminum targets with consistent orientation and uniform grain size.
Three annealing combined with hot rolling and cold rolling treatment were used to add trace amounts of cerium oxide through vacuum smelting, and multiple annealing and rolling treatments were performed to refine the grains of high-purity aluminum and improve its mechanical properties.
The fine and evenly distributed grain structure of high-purity aluminum targets is achieved, which improves its mechanical properties and sputtering properties, and improves welding properties, making it more suitable for large-size applications.
Smart Images

Figure BDA0005119648090000071 
Figure BDA0005119648090000081 
Figure BDA0005119648090000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-purity aluminum target materials, and particularly relates to a method for preparing a high-purity aluminum target material. Background Art
[0002] With the rapid development of the electronic information product manufacturing industry, especially in the manufacturing process of integrated circuits, thin film technology has been increasingly widely used. The film deposited by sputtering has a high density and is the main method for making metal films. The raw material used for sputtering thin film deposition is called a target material. Compared with raw aluminum, high-purity aluminum has better electrical conductivity, thermal conductivity, corrosion resistance, and low magnetic conductivity, and is an excellent target material.
[0003] However, the structure formed by high-purity aluminum targets during solidification is relatively coarse. Large plastic deformation is currently one of the most effective methods to obtain small and uniform grains, but this method can only produce products of smaller size. In addition, dynamic recrystallization is very likely to occur during the process, making it difficult to obtain high-purity aluminum targets with consistent orientation and uniform grain size. Therefore, a high-purity aluminum target with larger size, better grain uniformity and higher mechanical properties is urgently needed to meet the current market needs. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high-purity aluminum target material to solve the problems of small size, poor grain uniformity and poor mechanical properties of the high-purity aluminum target material.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] The present invention provides a method for preparing a high-purity aluminum target, comprising the following process steps:
[0007] S1. Surface finishing of high purity aluminum;
[0008] S2. The finely ground high-purity aluminum is preheated to 200-300°C, and a trace amount of cerium oxide is added for vacuum melting to obtain a high-purity aluminum ingot. The vacuum degree of vacuum melting is 1.0×10 -1 ~1.0×10 -2 Pa, melting temperature is 700-800℃, melting time is 30-60min;
[0009] S3. The high-purity aluminum ingot is annealed once at a temperature of 450 to 550°C for 2 to 3 hours, and then hot rolled at a temperature of 100 to 350°C.
[0010] S4. After hot rolling, the high-purity aluminum ingot is subjected to secondary annealing at a temperature of 100 to 300°C for 30 to 60 minutes, and then cold rolled, with cold water cooling between passes;
[0011] S5. Spraying the modified slurry on the surface of the high-purity aluminum ingot after cold rolling, and annealing three times after drying, the annealing temperature is 200-350° C., the annealing time is 1-2 h, and a high-purity aluminum target is obtained;
[0012] The modified slurry contains tetrapod-shaped zinc oxide whiskers.
[0013] Preferably, the added amount of cerium oxide is 0.002 to 0.005 wt %.
[0014] Preferably, the rolling deformation amount of the hot rolling treatment is 40-50%; and the rolling deformation amount of the cold rolling treatment is 80-90%.
[0015] Preferably, the addition amount of the four-needle zinc oxide whisker is 2-5% of the mass of the high-purity aluminum ingot after cold rolling.
[0016] By adopting the above technical scheme, the preparation method of the high-purity aluminum target provided by the present invention adopts three annealings combined with hot rolling and cold rolling treatment. The first annealing is to homogenize the high-purity aluminum ingot after vacuum melting, which will effectively improve the size, morphology and distribution of high-purity aluminum grains during the hot rolling process, and the influence of other impurity elements in high-purity aluminum on the performance of the high-purity aluminum target can be reduced through the first annealing. Specifically, this is conducive to the full precipitation of impurity elements such as iron, copper and silicon in the first annealing, reducing the grain boundary segregation caused by impurity elements, and promoting the uniformity of the orientation of high-purity aluminum grains; then, through hot rolling, secondary annealing, cold rolling and tertiary annealing, the internal grains of high-purity aluminum are gradually refined, and the distribution of grain size is kept uniform. The obtained high-purity aluminum target has a fine and uniformly distributed grain structure, and finally a large-size high-purity aluminum target with fine and uniformly distributed grains is obtained.
[0017] The purpose of adding a small amount of cerium oxide during the vacuum melting of high-purity aluminum is to introduce a small amount of cerium atoms during the melting process. The small amount of cerium atoms can serve as a grain refiner in the preparation of high-purity aluminum targets, inhibiting the growth of aluminum grains and preventing the increase of grain size, which helps to obtain high-purity aluminum targets with fine grains and improve the mechanical properties and sputtering processing performance of the targets. In addition, cerium atoms can also reduce cracks and pores generated during subsequent welding, thereby improving welding performance, making high-purity aluminum targets easier to weld, and expanding their application range. However, if the cerium atom content in the high-purity aluminum target is too high, second-phase particles will be formed at the internal two-phase grain boundary, which will not only affect the purity of the aluminum, but also become a crack source, causing internal stress concentration in the material, thereby reducing the ductility and toughness of the high-purity aluminum target.
[0018] After the cold rolling treatment, the present invention further performs surface treatment on the high-purity aluminum ingot, wherein the modified slurry contains four-needle zinc oxide whiskers, which have high hardness and good wear resistance, and can well improve the hardness and tensile strength of the high-purity aluminum target material, and enhance the mechanical properties of the high-purity aluminum target material. At the same time, the four-needle zinc oxide whiskers have a unique slender needle structure and a fibrous structure, and can form a reinforced network layer on the surface of the high-purity aluminum target material. Since aluminum is very easy to oxidize, this protective layer can well resist the effects of oxygen and other oxidants, and can also improve the surface corrosion resistance, wear resistance and thermal stability of the high-purity aluminum target material. In addition, the addition of four-needle zinc oxide whiskers can increase the roughness of the surface of the high-purity aluminum target material, thereby improving the adhesion of the coating or other surface treatment layers, which is beneficial to the subsequent application of the high-purity aluminum target material.
[0019] Preferably, the tetrapod-shaped zinc oxide whiskers are modified by aluminum doping.
[0020] Preferably, the molar ratio of aluminum to zinc in the tetrapod-shaped zinc oxide whiskers is (0.05-0.1):1.
[0021] Preferably, the tetrapod-shaped zinc oxide whiskers are aluminum-doped and modified according to the following method:
[0022] The organic aluminum salt is added to anhydrous ethanol, and the tetrapod-shaped zinc oxide whiskers are added, and the mixture is stirred and dispersed and then immersed for 2 to 3 hours. After filtering and drying, the mixture is heat treated at 850 to 950° C. for 2 to 3 hours, and then annealed at 600 to 700° C. for 4 to 5 hours in a nitrogen atmosphere to obtain aluminum-doped tetrapod-shaped zinc oxide whiskers.
[0023] More preferably, the organic aluminum salt includes a combination of one or more of aluminum isopropoxide, triethylaluminum and triisobutylaluminum.
[0024] By adopting the above technical solution, since the conductivity of the four-needle zinc oxide whisker is poor and the volume resistivity is high, after the surface treatment of the high-purity aluminum target, the conductivity and resistivity of the high-purity aluminum target will be affected to a certain extent, resulting in poor sputtering performance of the high-purity aluminum target in sputtering deposition, thereby affecting the performance of the metal film. Therefore, the four-needle zinc oxide whisker of the present invention is also modified by aluminum doping, which can significantly improve the conductivity of the four-needle zinc oxide whisker, and after aluminum doping modification, the interface bonding force between the four-needle zinc oxide whisker and the high-purity aluminum target is also significantly enhanced, further improving the tensile strength of the high-purity aluminum target, and at the same time, the bonding performance between the protective layer formed by the modified slurry and the high-purity aluminum target is improved, so that the internal high-purity aluminum target can be better and more durable protected.
[0025] Preferably, the modified slurry comprises the following raw materials in mass fractions: 10-30% of tetrapod-shaped zinc oxide whiskers, 1-5% of surfactant, 3-6% of aminosilane coupling agent, 0.5-2% of thickener and the remainder of solvent.
[0026] Preferably, the surfactant includes one or more combinations of polyvinyl pyrrolidone, polyethylene glycol, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.
[0027] Preferably, the thickener comprises a combination of one or more of carboxymethyl cellulose, xanthan gum and guar gum.
[0028] Preferably, the aminosilane coupling agent includes a combination of one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldiethoxysilane and anilinomethyltrimethoxysilane.
[0029] Preferably, the solvent includes a combination of one or more of ethanol, isopropanol, water, ethylene glycol, and n-butanol.
[0030] Preferably, the modified slurry is prepared according to the following method: tetrapod-shaped zinc oxide whiskers are uniformly dispersed in a solvent, and then a surfactant, an aminosilane coupling agent and a thickener are added, stirred and mixed, and after uniform mixing, the modified slurry is obtained by filtering.
[0031] By adopting the above technical scheme, the four-needle zinc oxide whiskers are first configured into a slurry, the surfactant can improve the dispersibility of the four-needle zinc oxide whiskers in the slurry, the aminosilane coupling agent can improve the interface bonding force between the four-needle zinc oxide whiskers and the high-purity aluminum target, and increase the surface wear resistance of the high-purity aluminum target; the thickener can adjust the slurry viscosity so that the modified slurry can be evenly sprayed on the surface of the high-purity aluminum target, which is helpful to form a uniform four-needle zinc oxide whisker protective layer and improve the various properties of the obtained high-purity aluminum target.
[0032] Beneficial effects of the present invention:
[0033] 1. The high-purity aluminum target of the present invention is added with a trace amount of cerium atoms through vacuum melting, which can refine the grains inside the high-purity aluminum target, help the obtained high-purity aluminum target to have a fine and evenly distributed grain structure, and improve the mechanical properties and sputtering properties of the high-purity aluminum target; at the same time, the addition of cerium atoms can also improve the welding performance of the high-purity aluminum target to a certain extent, and increase the scope of application. In addition, three annealings are combined with hot rolling and cold rolling treatments during the preparation process to promote the uniformity of the orientation of high-purity aluminum grains and promote the uniform refinement of grains.
[0034] 2. The surface of the high-purity aluminum target of the present invention is also treated with a modified slurry, and four-needle zinc oxide whiskers are added to the modified slurry. Its unique structural characteristics help to form a reinforced network layer on the surface of the high-purity aluminum target, thereby improving the mechanical properties and oxidation resistance of the high-purity aluminum target. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Preparation Example
[0037] Preparation Example 1: A modified slurry is prepared according to the following method:
[0038] Take 20g of four-needle zinc oxide whiskers (diameter 0.5-5μm, length 10-50μm) and evenly disperse them in 71g of isopropanol, then add 3g of polyvinyl pyrrolidone (model K30), 5g of γ-aminopropyltriethoxysilane and 1g of xanthan gum, stir and mix, mix evenly and filter to obtain a modified slurry.
[0039] Preparation Example 2, a modified slurry is prepared according to the following method:
[0040] Take 10g of four-needle zinc oxide whiskers (diameter of 0.5-5μm, length of 10-50μm) and evenly disperse them in 84g of isopropanol, then add 1g of polyvinyl pyrrolidone (model K30), 3g of γ-aminopropyltriethoxysilane and 2g of xanthan gum, stir and mix, mix evenly and filter to obtain a modified slurry.
[0041] Preparation Example 3, a modified slurry is prepared according to the following method:
[0042] Take 30g of four-needle zinc oxide whiskers (diameter 0.5-5μm, length 10-50μm) and evenly disperse them in 58.5g of isopropanol, then add 5g of polyvinyl pyrrolidone (model K30), 6g of γ-aminopropyltriethoxysilane and 0.5g of xanthan gum, stir and mix, mix evenly and filter to obtain a modified slurry.
[0043] Preparation Example 4, a modified slurry, which differs from Example 1 only in that the unmodified tetrapod-shaped zinc oxide whiskers are replaced with an equal amount of aluminum-doped modified tetrapod-shaped zinc oxide whiskers;
[0044] The aluminum-doped modified tetrapod-shaped zinc oxide whiskers were prepared according to the following method:
[0045] 0.1 mol of aluminum isopropoxide was added to 500 mL of anhydrous ethanol, and 1 mol of tetrapod-shaped zinc oxide whiskers was added. After stirring and dispersing, the mixture was immersed for 2 h. After filtering and drying, the mixture was heat treated at 900 ° C for 2 h, and then annealed at 600 ° C for 5 h in a nitrogen atmosphere to obtain aluminum-doped tetrapod-shaped zinc oxide whiskers.
[0046] Preparation Example 5, a modified slurry, is different from Example 4 only in that the molar ratio of aluminum to zinc in the aluminum-doped modified tetrapod-shaped zinc oxide whiskers is 0.05:1.
[0047] Preparation Example 6, a modified slurry is prepared according to the following method:
[0048] 3 g of polyvinyl pyrrolidone (model K30), 5 g of γ-aminopropyltriethoxysilane and 1 g of xanthan gum were added to 91 g of isopropanol, and the mixture was stirred and mixed. After the mixture was evenly mixed, the modified slurry was obtained by filtering.
[0049] Example
[0050] Example 1: A high purity aluminum target is prepared according to the following process steps:
[0051] S1. Surface finishing of 5N5 high purity aluminum;
[0052] S2. The finely ground high-purity aluminum was preheated to 250°C, and 0.003wt% cerium oxide was added for vacuum melting to obtain a high-purity aluminum ingot, wherein the vacuum degree of vacuum melting was 1.0×10 -1 Pa, melting temperature is 800℃, melting time is 30min;
[0053] S3. The high-purity aluminum ingot is annealed once at a temperature of 500°C for 2 hours, and then hot rolled at a temperature of 200°C and a rolling deformation of 50%;
[0054] S4. After hot rolling, the high-purity aluminum ingot is subjected to secondary annealing at a temperature of 150°C for 60 minutes, and then cold rolled, with cold water cooling between passes, and a rolling deformation of 90%;
[0055] S5. After cold rolling, the modified slurry prepared in Preparation Example 1 is sprayed on the surface of the high-purity aluminum ingot, and the addition amount of the four-needle zinc oxide whiskers is controlled to be 4wt% of the high-purity aluminum ingot. After drying, annealing is performed three times, the annealing temperature is 300°C, and the annealing time is 1h to obtain a high-purity aluminum target.
[0056] Example 2, a high-purity aluminum target, is different from Example 1 only in that the added amount of cerium oxide is 0.002 wt%.
[0057] Example 3, a high-purity aluminum target, is different from Example 1 only in that the added amount of cerium oxide is 0.005wt%.
[0058] Example 4, a high-purity aluminum target, is different from Example 1 only in that the addition amount of the four-needle zinc oxide whiskers in the modified slurry prepared in Preparation Example 1 is 2wt% of the high-purity aluminum ingot.
[0059] Example 5, a high-purity aluminum target, is different from Example 1 only in that the addition amount of the four-needle zinc oxide whiskers in the modified slurry prepared in Preparation Example 1 is 5wt% of the high-purity aluminum ingot.
[0060] Embodiment 6 and Embodiment 7 are high purity aluminum target materials. The only difference from Embodiment 1 is that the process parameters and raw materials in the preparation process are adjusted, as shown in Table 1:
[0061] Table 1 Process parameter comparison table of Example 1, Example 6 and Example 7
[0062]
[0063]
[0064] Among them, Example 6 uses an equal amount of the modified slurry prepared in Preparation Example 2; Example 7 uses an equal amount of the modified slurry prepared in Preparation Example 3.
[0065] Example 8, a high purity aluminum target material, is different from Example 1 only in that the modified slurry prepared in Preparation Example 1 is replaced by an equal amount of the modified slurry prepared in Preparation Example 4.
[0066] Example 9, a high purity aluminum target material, is different from Example 1 only in that the modified slurry prepared in Preparation Example 1 is replaced by an equal amount of the modified slurry prepared in Preparation Example 5.
[0067] Example 10, a high-purity aluminum target material, is different from Example 1 only in that the addition amount of the four-needle zinc oxide whiskers in the modified slurry prepared in Preparation Example 1 is 1wt% of the high-purity aluminum ingot.
[0068] Example 11, a high-purity aluminum target material, is different from Example 1 only in that the addition amount of the four-needle zinc oxide whiskers in the modified slurry prepared in Preparation Example 1 is 6wt% of the high-purity aluminum ingot.
[0069] Example 12, a high-purity aluminum target material, is different from Example 1 only in that the rolling deformation amount of the hot rolling treatment is 30%.
[0070] Example 13, a high-purity aluminum target material, is different from Example 1 only in that the rolling deformation amount of the hot rolling treatment is 60%.
[0071] Example 14, a high-purity aluminum target material, is different from Example 1 only in that the rolling deformation amount of the cold rolling treatment is 70%.
[0072] Example 15, a high-purity aluminum target material, is different from Example 1 only in that the rolling deformation amount of the cold rolling treatment is 95%.
[0073] Comparative Example
[0074] Comparative Example 1 is a high-purity aluminum target material, which is different from Example 1 only in that the addition amount of cerium oxide is 0.008 wt %.
[0075] Comparative Example 2 is a high-purity aluminum target material, which is different from Example 1 only in that cerium oxide is not added.
[0076] Comparative Example 3, a high purity aluminum target material, is different from Example 1 only in that the modified slurry prepared in Preparation Example 1 is replaced by an equal amount of the modified slurry prepared in Preparation Example 6.
[0077] Comparative Example 4 is a high-purity aluminum target material, which is different from Example 1 only in that the modified slurry prepared in Preparation Example 1 is not sprayed on the surface of the high-purity aluminum ingot after cold rolling.
[0078] Comparative Example 5 is a high-purity aluminum target material, which is different from Example 1 only in that no annealing treatment is performed.
[0079] Performance testing:
[0080] 1. Mechanical properties test:
[0081] (1) Hardness test: The hardness of the high-purity aluminum target obtained in the embodiment and the comparative example was measured using a Vickers microhardness tester;
[0082] (2) Tensile properties test: According to the relevant records in GB / T 228.1-2021 "Tensile test of metallic materials Part 1: Room temperature test method", the tensile properties of the high-purity aluminum target materials obtained in the examples and comparative examples were tested.
[0083] 2. Sputtering performance test: A high vacuum multi-target magnetron sputtering coating machine was used to perform magnetron sputtering coating, and the resistivity of the sputtered films of the high-purity aluminum target materials obtained in the embodiments and comparative examples was tested.
[0084] The above test results are shown in Table 2:
[0085] Table 2 Performance test results
[0086]
[0087] According to Table 2, in combination with Example 1 and Example 2 to Example 7, it can be seen that the hardness, tensile strength and sputtered film resistivity of Example 2 to Example 7 are not significantly different from those of Example 1, indicating that the mechanical properties and sputtering properties of Example 2 to Example 7 are not much different from those of Example 1. The reason is that, compared with Example 1, Example 2 to Example 7 only change the raw material ratio and process parameters within the required range, which has little effect on the material properties.
[0088] Combining Example 1, Example 8 and Example 9, it can be seen that the hardness and tensile strength of Example 8 and Example 9 are slightly improved compared with Example 1, and the resistivity of the sputtered film is significantly reduced. The reason is that the four-needle zinc oxide whiskers used in Example 8 and Example 9 are modified by aluminum doping, and the conductivity is significantly improved. In addition, the aluminum doping improves the bonding force between the modified slurry and the high-purity aluminum target material, and the mechanical properties are also slightly improved.
[0089] Combining Example 1, Example 10, Example 11, Comparative Example 3 and Comparative Example 4, it can be seen that the hardness and tensile strength of Example 10, Example 11, Comparative Example 3 and Comparative Example 4 are all reduced compared to Example 1, and the resistivity is increased, and the reduction in Comparative Example 3 and Comparative Example 4 is more obvious. The reason is that the content of four-needle zinc oxide whiskers in the surface treatment process is changed in Example 10, Example 11, Comparative Example 3 and Comparative Example 4. The whisker content is reduced in Example 10, resulting in a decrease in the density of the protective layer formed on the surface of the high-purity aluminum target material, and a decrease in the ability to improve the mechanical properties of the material. Four-needle zinc oxide whiskers are not added in Comparative Example 3 and Comparative Example 4, and the effect of improving the performance is significantly reduced. The whisker content is increased in Example 11, which will cause the conductivity of the material to decrease and the resistivity to increase.
[0090] Combining Example 1 and Example 12 to Example 15, it can be seen that the hardness and tensile strength of Example 12 to Example 15 are reduced compared with Example 1, and the resistivity is increased. The reason is that compared with Example 1, Example 12 to Example 15 changes the rolling deformation during hot rolling and cold rolling. Specifically, in Example 12 and Example 14, the rolling deformation of hot rolling and cold rolling is reduced respectively, the grains inside the high-purity aluminum target have not been redistributed and the recrystallization phenomenon that occurs is greatly reduced, and the grains of the high-purity aluminum target have not been able to be refined in time, and the mechanical properties and sputtering properties of the material are reduced; in Example 13 and Example 15, the rolling deformation of hot rolling and cold rolling is increased respectively. Too much deformation will cause serious deformation of the grains, forming a flattened structure, which is not conducive to the improvement of the mechanical properties of the material. Moreover, too much deformation will cause a large amount of residual stress to accumulate inside the high-purity aluminum target during the rolling process, which is difficult to completely eliminate by annealing, thereby increasing the probability of cracks and reducing mechanical properties.
[0091] Combining Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the hardness and tensile strength of Comparative Example 1 and Comparative Example 2 are significantly reduced compared with Example 1, and the resistivity is significantly increased, indicating that the mechanical properties and sputtering properties of Comparative Example 1 and Comparative Example 2 are significantly reduced compared with Example 1. The reason is that the amount of cerium oxide added is changed in Comparative Example 1 and Comparative Example 2, wherein excessive cerium oxide is added in Comparative Example 1. The excessive introduction of cerium atoms will lead to the formation of second phase particles at the two-phase grain boundary inside the high-purity aluminum target, resulting in internal stress concentration of the material and reducing the mechanical properties of the material.
[0092] Combining Example 1 and Comparative Example 5, it can be seen that the hardness and tensile strength of Comparative Example 5 are significantly reduced compared with Example 1, and the resistivity is significantly increased, indicating that the mechanical properties and sputtering properties of Example 5 are significantly reduced compared with Example 1. The reason is that Comparative Example 5 has not undergone an annealing treatment compared with Example 1. After vacuum melting, defects and stress concentration points will exist in the high-purity aluminum target material. If they are not eliminated by annealing, it will affect the growth and distribution of grains during hot rolling and cold rolling. At the same time, the residual impurity elements will affect the orientation of the high-purity aluminum target material, resulting in a decrease in various properties of the material.
[0093] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0094] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-purity aluminum target, characterized in that: The process steps include: S1. Surface finishing of high purity aluminum; S2. The finely ground high-purity aluminum is preheated to 200-300°C, and a trace amount of cerium oxide is added for vacuum melting to obtain a high-purity aluminum ingot. The vacuum degree of vacuum melting is 1.0×10 -1 ~1.0×10 -2 Pa, melting temperature is 700-800℃, melting time is 30-60min; S3. The high-purity aluminum ingot is annealed once at a temperature of 450 to 550°C for 2 to 3 hours, and then hot rolled at a temperature of 100 to 350°C. S4. After hot rolling, the high-purity aluminum ingot is subjected to secondary annealing at a temperature of 100 to 300°C for 30 to 60 minutes, and then cold rolled, with cold water cooling between passes; S5. Spraying the modified slurry on the surface of the high-purity aluminum ingot after cold rolling, and annealing three times after drying, the annealing temperature is 200-350° C., the annealing time is 1-2 h, and a high-purity aluminum target is obtained; The modified slurry contains tetrapod-shaped zinc oxide whiskers.
2. The method for preparing a high purity aluminum target according to claim 1, characterized in that: The added amount of the cerium oxide is 0.002-0.005 wt %.
3. The method for preparing a high purity aluminum target according to claim 1, characterized in that: The rolling deformation amount of the hot rolling treatment is 40-50%; the rolling deformation amount of the cold rolling treatment is 80-90%.
4. The method for preparing a high purity aluminum target according to claim 1, characterized in that: The addition amount of the four-needle zinc oxide whisker is 2-5% of the mass of the high-purity aluminum ingot after cold rolling.
5. The method for preparing a high purity aluminum target according to claim 1, characterized in that: The four-needle zinc oxide whiskers are modified by aluminum doping.
6. The method for preparing a high purity aluminum target according to claim 5, characterized in that: The molar ratio of aluminum to zinc in the four-needle zinc oxide whisker is (0.05-0.1):
1.
7. The method for preparing a high purity aluminum target according to claim 1, characterized in that: The modified slurry comprises the following raw materials in mass fractions: 10-30% of tetrapod-shaped zinc oxide whiskers, 1-5% of surfactants, 3-6% of aminosilane coupling agents, 0.5-2% of thickeners and the remainder of solvents.
8. The method for preparing a high purity aluminum target according to claim 7, characterized in that: The surfactant includes one or more combinations of polyvinyl pyrrolidone, polyethylene glycol, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.
9. The method for preparing a high-purity aluminum target according to claim 7, characterized in that: The thickener includes a combination of one or more of carboxymethyl cellulose, xanthan gum and guar gum.
10. The method for preparing a high purity aluminum target according to claim 7, characterized in that: The modified slurry is prepared according to the following method: tetrapod-shaped zinc oxide whiskers are uniformly dispersed in a solvent, and then a surfactant, an aminosilane coupling agent and a thickener are added, stirred and mixed, and after uniform mixing, the modified slurry is obtained by filtering.